J. Daniel Hays, The Temple and the Tabernacle. A Study of God’s Dwelling Places from Genesis to Revelation (Grand Rapids, MI: Baker Books 2016) - Kubiś, Adam (The Biblical Annals, 2018)
Book of review: J. Daniel Hays, The Temple and the Tabernacle. A Study of God’s Dwelling Places from Genesis to Revelation (Grand Rapids, MI: Baker Books 2016). Pp. 208. 19.99. ISBN 9780801016202 (Paperback). DOI: https://doi.org/10.31743/ba.2018.8.2.09